Enterprise Integration of Employee Onboarding Process Using Zachman Framework - Faezah Abbas, Wan; Hajar Ismail, Siti; Haron, Haryani; Nor Amalina Wan Hariri, Wan (International Journal of Engineering and Technology, 2018)
Onboarding is the process of getting newly hired employee to adjust to the social and performance aspects of their new jobs quickly and smoothly. It is important to the organization to maximize the employee retention and productivity and increase their satisfaction and loyalty where it could reduce cost of hiring employee by reducing the turnover rate. Studies have shown there is a requirement to integrate the business process between the enterprise entities to make the onboarding processes run smoothly and effectively. Therefore, the main objective of this study is to analyze the business processes to be integrated in the enterprise organization. Using qualitative methods, interview and document review, analysis was conducted to understand the current onboarding practices and processes in a case study. As a result, this research proposes a business process driven modelling for analysing enterprise integration requirements by using Zachman framework. Â